Key learnings from COVID‐19 to sustain quality of life for families of individuals with IDD. Issue 1 (30th March 2022) - Wanjagua, Rachael; Hepburn, Stevie‐Jae; Faragher, Rhonda; John, Shaji Thomas; Gayathri, K.; Gitonga, Margaret; Meshy, Cecylia Francis; Miranda, Lucena; Sindano, Devis
Abstract: COVID‐19 has very publicly had profound impacts on the health system of every country in the world. Over 4.5 million people have lost their lives. School closures worldwide where up to 1.6 billion of the world's children have been out of school, are also prominent in world news. Behind these public impacts are the families. In this paper, we focus on the experiences of families with people with intellectual and developmental disabilities (IDD) through analysis of two data sets: the emerging research literature and contributions from our author team who have lived experience of intellectual and developmental disability in the context of COVID‐19. From these two data sets, we discern five themes of the impact of the pandemic: on health, on education, on services and supports, on families and finally on relationships beyond the family. We conclude with lessons from those living with intellectual and developmental disabilities, the carers and the individuals themselves to draw implications for supporting families in the context of disability during future pandemics.